Impactand particle buffered vibration absorbers optimization and design - Diveyev, Bohdan (Publishing House of Lviv Polytechnic National University, 2015)
Passive, broadband targeted energy transfer refers to the one-way directed transfer of energy from a primary subsystem to a nonlinear attachment; this phenomenon is realized in damped, coupled, essentially nonlinear impact or particle dynamic vibration absorber (DVA). An impact damper is a passive control device which takes the form of a freely moving mass, constrained by stops attached to the structure under control, i.e. the primary structure. The damping results from the exchange of momentum during impacts between the mass and the stops as the structure vibrates. A particle-based damping system can overcome some limitations of ordinary DVA by using particles as the damping medium and inter- particle interaction as the damping mechanism. Large damping at such family constructions of DVA’s does not bring to destruction an elastic DVA element over in critical cases, when working frequency approaches own frequency of DVA, or when the transitional process of acceleration of rotating machines is slow enough and DVA’s has time to collect large amplitudes of vibrations. The primary structure is modelled as a spring-mass system. In this paper, an efficient numerical approach based on the theoretical-experimental method is proposed to maximize the minimal damping of modes in a prescribed frequency range for general viscous tuned-mass systems. Methods of decomposition and numerical synthesis are considered on the basis of the adaptive schemes. The influence of dynamic vibration absorbers and basic design elastic and damping properties is under discussion. A technique is developed to give the optimal DVA’s for the elimination of excessive vibration in sinusoidal forced rotating system. It is found that the buffered impact damper not only significantly reduces the accelerations, contact force and the associated noise generated by a collision but also enhances the level of vibration control. The interaction of DVA’s and basic design elastic and damping properties is under discussion. One task of this work is to analyze parameters identification of the dynamic vibration absorber and the basic structure. The discrete-continue models of machines dynamics of such rotating machines as water pump with the attachment of particle DVA’s and elongated element with multi mass impact DVA’s are offered. A technique is developed to give the optimal DVA’s for the elimination of excessive vibration in harmonic stochastic and impact loaded systems.